Genetic association study of KCNB1 gene with the susceptibility of hypertension related Left Ventricular Hypertrophy (LVH) patients in Malaysia / Hoh Boon Peng and Khalid Yusoff - Hoh, Boon Peng; Yusoff, Khalid (Research Management Institute (RMI), 2012)
Left ventricular hypertrophy (LVH) is an independent risk factor for the development of heart failure, coronary heart disease and stroke. It develops as a result of hemodynamic overload, for instance, hypertension (Gary et al., 2007). Blood pressure is an important determinant of LVH, and significant proportion of patients with essential hypertension develops their complication. However, this disease varies in a wide range of phenotype, and studies had shown that patients with LVH may have near-normal blood pressure, suggesting that development of LVH may be an independent genetic factor from hypertension. This proposed study hence, attempts to verify the study by replicating the finding in our population, ie studying the SNPs of the KCNB1 gene among the hypertensive patients with LVH. We have genotyped earlier 100 subjects on the SNP rs6063397. We noted that this SNP is in full linkage disequilibrium with rs756529 (D’ = 1: r2 =1). Therefore in this study, we attempted to genotype rs6063397 in additional 100 subjects with hypertension and/or with left ventricular hypertrophy. Of the total 200 hypertensive subjects, 61 were LVH and 139 were non LVH. These subjects were genotyped using sequencing. No association was observed between both alleles and genotypes of rs6063397 LVH susceptibility suggesting that KCNB1 may not play role in LVH susceptibility in hypertensive patients in Southeast Asian populations.